Desigualdades de Hitchin-Thorpe e Miyaoka-Yau - Rodrigues, Diego de Sousa (2014)
The aim of this work is to present a proof of the Hitchin-Thorpe and Miyaoka-Yau inequalities. First we provide an orthogonal decomposition for the curvature tensor, and then we show how the curvature operator can be defined from the curvature tensor. In order to fulfill the proposed objective, we prove the Gauss-Bonnet Theorem in dimension 4, to do this we use a result due Allendoerfer and we present an integral formula for the Euler characteristic computation on a Riemannian 4-manifold. Furthermore, we define the concept of signature in a Riemannian manifold e we exhibit an integral formula for the achievement of this object, for this we use the Hirzebruch Signature Theorem in di- mension 4 and the Chern-Weil Theory which provides us a connection between algebraic topology and differential geometry. Finally, we show how the earlier formulas can be used in the demonstration of the initial inequalities.